(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tomato plants are highly sensitive to chilling stress so this experiment was conducted during successive winter seasons of 2020/2021 and 2021/2022 to investigate the possibility of sustaining production and quality of tomato yield under cold conditions by using different types of mesh cover for low tunnels. Two commercial cultivars, i.e., Super gold F1 and Super streen F1 were used. Seedlings were transplanted under different types of mesh cover for low tunnels. Three types of mesh cover (63%, 65%, 73%) had done to cover the plants of all tested seasons compared to open field condition (control "Without cover"). Results show that significant differences were observed among the two hybrid varieties of tomato studied, in terms of their vegetative growth characteristics (plant height, number of branches, number of leaves, fresh weight, dry weight and leaves area) as well as yield and fruit quality characteristics (Fruit set, total yield, firmness, T.S.S and Vit. C. ‘Super gold’ exhibited significantly higher values for these characteristics, compared to ‘Super strain B’. Chilling reduced the growth parameters (plant height, number of leaves, number of branches, plant fresh weight, plant dry weight) for control plants (without cover) compared to the coverage treatments (63%, 65%, 73%). Significant highest results in the growth, chemical composition of tomato leaves as well as yield and fruit quality parameters were obtained with covering tomato plants by white mesh cover 63% flowed by 65% of treatments which were best than the chilled plants. Concerning the interaction between hybrid varieties and covering treatments, it can be noticed that Cv. Super gold F1 which grown under white mesh cover 63% recorded a highly significant increases in plant height, number of branches, number of leaves, fresh weight, dry weight, leaves area, N, P, K, total chlorophyll, total proline, total sugers contents, fruit set, total yield, firmness, T.S.S and Vit. C. when compared to Cv. Super streen B F1 which grown in open field (without coverage).